Jacques Derrida - Buongiorno, Federica (Philosophy Kitchen - Rivista di filosofia contemporanea, 2024)
In the impossibility of explaining without trivialisation why a thinker of the calibre of Jacques Derrida - whose trajectories Diego D’Angelo reconstructs in the contribution that follows this short introduction - has been decisive in the (internal and external) perspective outlined by Philosophy Kitchen over the last ten years, I leave the floor to Judith Butler, who beautifully described his life and work in the aftermath of his death in 2004.